Ensino de física e o impacto da experimentação de baixo custo no último ano do nível médio. - FURTADO, Jonas Diniz (2024)
With numerous ways of teaching and transmitting knowledge, it is essential to study them in order to establish which one is most suitable for a specific area of knowledge. Therefore, this paper discusses the teaching of physics from the perspective of students to gain a clearer idea of which methods to use and how to use them correctly. The methodology applied in this research is low-cost experimental experimentation, considering that the high cost of advanced equipment for physical experimentation makes it unfeasible for most schools. Thus, low-cost experimentation becomes an attractive option to make physics more tangible and interesting for students. The methodology was implemented at Izabel dos Santos Dias State School, which lacks a physics laboratory and faces serious structural issues, further supporting the idea of using low-cost experiments. Throughout the process, a significant interaction and increased motivation of the 42 students were observed with this new way of studying physics, which can be interpreted as a positive outcome.